Factors that Influence Learning Outcomes and Nutritional Knowledge of Students Majoring in Family Welfare Education and Culinary Arts at Universities - Polii, Henny Jeane (International Journal of Information Technology and Education, 2024)
This research aims to identify factors that have the potential to influence the learning outcomes and nutritional knowledge of students majoring in PKK Culinary Arts at Manado State University. Students in this major are expected to have a deep understanding of culinary and nutrition, so their learning outcomes are crucial in determining the quality of graduates. Through an approach, this research method uses a quantitative approach with survey techniques using a structured questionnaire. The research sample will be randomly selected from active semester students in the PKK Culinary Management Department, Manado State University. The data obtained will be analyzed using descriptive and inferential statistical techniques. Factors considered include educational background, motivation, study habits, access to learning resources and nutritional information, and other environmental factors. The factors that will be studied include internal variables, such as learning motivation, lecture attendance, and independent study time, and external variables, such as family support, learning facilities, and social environment. Apart from that, this research will also measure students’ level of nutritional knowledge and relate it to their learning outcomes. This research has the potential to provide an in-depth understanding of the relationship between various factors and learning outcomes and nutritional knowledge of students majoring in PKK Culinary Arts. It is hoped that the research findings can provide valuable input for curriculum development, learning strategies, and the provision of more effective educational resources in the Manado State University PKK Culinary Educational environment. Thus, it is hoped that this research can contribute to improving the quality of education and understanding of nutrition among PKK Culinary Arts students and society in general.